Influence of absorption level on mechanisms of Braggdiffracted x-ray beam formation in real silicon crystals - Klad'ko, V. P.; Grigoriev, D.O.; Datsenko, L.I.; Machulin, V.F.; Prokopenko, I.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
The methods of numerical calculations based on the formulae of the X-ray dynamic scattering theory by real crystals and of the Takagi-Topin equations were used for investigation of the basic regularities of inherent to the Bragg diffraction in conditions of a strong and weak absorption. The mechanisms of profile formation of a spatial intensity distribution of diffracted beams depending on an energy of radiation and on structural perfection parameters of crystals are discussed. The formulae for an analytical description of spatial intensity distribution profiles which take into account the dynamical corrections (coefficients of extinction) for coherent and incoherent components of the total reflectivity were used.